Identification of change leadership dimensions and components in medical science education to move toward the third-generation universities: A qualitative study - Ghobad Ramezani; Shoaleh Bigdeli; Yadolah Zarezadeh; Zohreh Sohrabi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Change is a multidimensional and pervasive issue in the modern world, and organizations are constantly changing in social, cultural, political, economic, and technological fields. Change leadership is a model that employs a combination of leadership styles to keep the employees and the organization prepared for learning and continuous growth. This study aims to identify the dimensions and components of change leadership in medical sciences education to move toward third-generation universities through a qualitative approach. MATERIALS AND METHODS: The present study was an applied explorative qualitative study. Participants included the experts in the field of management and key informants in the field of change leadership and third-generation universities who were selected through purposive sampling. The research tool was semi-structured interviews aimed at the identification of dimensions and components of the change leadership. Interview-guided questions were about change leadership to move toward the third-generation universities followed by probing questions. Colaizzi content analysis technique was used to analyze the data. RESULTS: Data from interview transcript analysis resulted in the identification of 335 initial codes, 13 subcategories, and 3 categories or dimensions. The main categories included "change leadership roles and specifications," "providing a context and preparing for change," and "change leadership process and path." Each of the main dimensions included several components. CONCLUSION: The importance of leadership in the process of change is since change entails the establishment and institutionalization of new systems and structures which is impossible without an effective leadership style. Leaders have high expectations of their followers and inspire them to strive toward organizational goals and facilitate the realization of the shared vision through encouraging them. As a leadership paradigm for organization performance improvement capable of encouraging employees and building an organizational culture in which ethical procedures are considered behavioral norms, change leadership seeks to predict the environment changes so that it can move in accordance with them.